Emergency Report System Multi-Channel Notification Berbasis Web pada Dinas Damkar Kabupaten Kediri - Erlangga Fajar Ramadhan Ramadhan; Rini Indriati; Dwi Harini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Conventional emergency reporting at the Kediri Regency Fire Department suffers from three structural problems: location inaccuracy, the absence of self-tracking for the public, and unstructured documentation. Similar studies typically address these issues separately, without integrating automatic geolocation, multi-channel notification, role-based access control (RBAC), and security validation into one empirically tested system. This study develops a web-based Emergency Response Information System (SIRTADA) using the Waterfall method, with a three-tier architecture combining automatic geolocation, Firebase Cloud Messaging, and a WhatsApp Gateway as parallel notification channels. Multi-level evaluation shows solid results: 100% unit test pass rate (63 test cases), 97.5% integration test pass rate (78/80 assertions), and an 89.3% UAT score (